From cash flows to water flows: An assessment of financial risks to rural water supply sustainability in sub-Saharan Africa - Foster, T (2016)
This research examines the collective action and financial dimensions of rural waterpoint sustainability in sub-Saharan Africa. Four interlinking papers empirically evaluate the nature and drivers of financial risks, and how they in turn impact the operational performance of community water supplies. The research is grounded in conceptual and theoretical frameworks pertaining to collective action and common-pool resource management, in particular Ostrom's social-ecological systems framework (Ostrom, 2007), Musgrave & Musgrave's economic good framework (Musgrave & Musgrave, 1973), and Marwell & Oliver’s critical mass theory (Marwell & Oliver, 1993). The first paper analyses data extracted from national waterpoint inventories in Liberia, Sierra Leone, and Uganda. The remaining three papers draw on primary data from rural Kenya comprising 229 years' worth of water committee financial records, a census of 571 waterpoints, and a survey of 3,361 households. These data were collected during extensive field work campaigns in Kwale, Kenya. Quantitative analyses were carried out by way of advanced statistical techniques, including logistic regression, linear mixed (repeated measure) models, and generalised estimating equations. Results suggest collection of user fees is a significant determinant of waterpoint sustainability, alongside other institutional, technical, geographical and environmental variables. However, monthly payment arrangements are beset by non-payment and late payment, particularly if rainfall levels are high, group size is large, households are far away, and water is aggressive and unpalatable. Although monthly contribution levels remain relatively stable above a collective payment rate of 60%, there is little evidence of self-sustaining growth beyond this point, and revenue collection is prone to collapse below this collective payment threshold. In comparison, pay-as-you-fetch fees are associated with increased revenue and improved operational performance, but result in a higher proportion of households opting for an unimproved water source. If the Sustainable Development Goal of universal access to safe water supplies is to be achieved in rural sub-Saharan Africa, strategies are needed to strengthen revenue collection systems and bolster payment incentives. External support and professionalised service delivery models present potential pathways to advance these goals. Policymakers may also need to introduce carefully designed subsidies, or promote self-supply approaches that realign lifecycle costs with users’ willingness-to-pay.